2016
DOI: 10.1177/2150135116663697
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Technique for Interventional Extracardiac Fontan

Abstract: Our technique of interventional Fontan, anatomically and hemodynamically, mimics a standard ECF procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…49 Still, it has been shown that interventional creation of a superior cavopulmonary connection with the usage of long covered stents, 39 intervascular connections as the interventional Potts shunt, 50 or interventional completion of Fontan are possible in animals and also in humans. 40,[42][43][44][45][46][47][48]51 The different anatomical features in animals and the nowadays limited availability of endovascular catheter materials make the creation of a solely interventional superior cavopulmonary connection difficult. Most likely, such a procedure will result in a connection between the SVC and the right lower lobe PA, directing most of the blood flow to the right lower lobe.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…49 Still, it has been shown that interventional creation of a superior cavopulmonary connection with the usage of long covered stents, 39 intervascular connections as the interventional Potts shunt, 50 or interventional completion of Fontan are possible in animals and also in humans. 40,[42][43][44][45][46][47][48]51 The different anatomical features in animals and the nowadays limited availability of endovascular catheter materials make the creation of a solely interventional superior cavopulmonary connection difficult. Most likely, such a procedure will result in a connection between the SVC and the right lower lobe PA, directing most of the blood flow to the right lower lobe.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Covered stents have a continually expanding spectrum of applications for patient with congenital heart disease. Their use has been described for Fontan completion for over a decade [3][4][5] and there is an established precedent for their use in redirection of blood flow in the setting of complex CHD repair. 6 For this to become a more generalized approach, it will require anticipation and changes to the surgical technique to "setup" for future percutaneous intervention.…”
Section: Discussionmentioning
confidence: 99%
“…2 In 2017, Prabhu and coworkers in Brisbane, Australia, building upon strategies proposed by numerous clinician-investigators as early as the mid-90s, described an innovative procedure to prepare a fiveyear-old patient with single ventricle for eventual completion of the Fontan circulation by means of an interventional catheterization procedure. 1,3 At the time of the Glenn procedure, they sutured a short ePTFE conduit to the right pulmonary artery and another longer graft to the IVC. A large medial opening made in the lower conduit was anastomosed side-to-side to a right atriotomy.…”
Section: Commentmentioning
confidence: 99%